Pendampingan Pengelolaan Website Sekolah Berbasis Content Management System di SD Xaverius 9 Palembang - Triayomi, Ria; Setyo Wibagso, Stefanus; Sukarman, Sukarman; Putera Setiahati, Ignasius; Lili Sugiarti, Geovani; Devita Ningrum, Natalia; Esti Putri Utaminingrum, Emilia (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service was carried out by a team of lecturers from PGSD Study Program and Information Systems Study Program with Partner Schools at Xaverius 9 Elementary School Palembang. "Content Management System-Based School Website Management Assistance at SD Xaverius 9 Palembang". The application of information technology in schools, one of which is the provision of a school website as a medium for disseminating information and communication between schools and related parties. Having a school website has several benefits, including being present in providing positive content for the public to create a healthy internet, encouraging schools to provide positive and creative information on school activities, student guardians and the community can find out various things about the school directly, and foster community trust in schools. The purpose of this activity is to assist website managers in writing good news so that it is easily searchable by search engines and attracts readers. The hope of assistance is that the website can be tracked using a tracking engine and appears on the first page. Implementation of assistance by providing assistance and practice regarding making good news, and media processing.